Synthesis and characterization of MCM-41 and use as a catalyst in friedel-crafts reaction - 420908 Ang, Boon Kim; Halimaton Hamdan, supervisor; Fakulti Sains (Skudai : Universiti Teknologi Malaysia, 2000)
Thesis (Master of Science (Chemistry)) - Universiti Teknologi Malaysia, 2000